Uso de esgoto doméstico tratado no desenvolvimento da cultura do feijão-caupi em ambiente protegido - Silva, Elis Lei da (2019)
The use of water in irrigating crops without proper management has led to waste of a resource that has become increasingly scarce in many regions of the world. The increase in population has led to a higher consumption of water and consequently to the increase of the generated domestic effluent, which often returns to the environment with inadequate treatment. The use of adequate management of irrigation and treated domestic effluents has been an alternative to reduce waste and provide a greater share of good quality water to supply populations. Thus, the reuse of domestic effluent treated in irrigated agriculture is an alternative so that the amount requested by the sector is contemplated without prejudice to the public supply and the watering of animals, which are priority uses, besides avoiding possible contamination of the water sources. In this context, the objective of this work was to evaluate the growth and production of cowpea (Vigna unguiculata (L.) Walp.) with different irrigation depthsand concentrations of treated domestic effluent. The experiment was conducted in a randomized block design (DBC) in a 3 x 4 factorial scheme grown in a protected environment located at the Federal University of Sergipe. The culture was submitted to three concentrations of effluent (0, 50 and 100%); four irrigation slides corresponding to 75, 100, 125 and 150% of crop evapotranspiration (ETc) and four replications, totalizing 48 vessels. For irrigation control, an automatic meteorological station installed in the protected environment was used. The irrigation slides corresponding to 150% of ETc when applied with 100% treated domestic effluent provided higher plant height and shoot diameters, but did not result in larger leaf numbers and root system. Soil salinity affected bean production. The thermotolerant coliform contents of the treated domestic effluent used in the irrigation of the beans were outside the standards recommended by the National Council for the Environment - CONAMA and the World Health Organization - WHO for irrigation water.